2000
DOI: 10.1080/10402000008982389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ceramic Tools in Hard Turning of Hardened AISI M2 Steel

Abstract: Tool wear and machining performance of hardened AISI M2 steel in hard turning has been studied. Ceramic tools were used in the cutting tests without coolants, and the workpiece was heat treated to increase its hardness up to Rc 60. Cutting forces, temperature, and tool wear were measured in the experiments and the effects of cutting conditions on these were investigated. Important aspects from the research are summarized as follows:I . Flank wear was the dominant wear mode on the ceramic tool insert in hard tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…It was concluded that the cutting speed was found to be the most important parameters on the tool life among control parameters. Similar results were obtained with previous works carried out by Lima et al (2005), Jang and Hsiao (2000), Sahin and Sur (2005), Sahin (2006), Benga and Abrao (2003), Chou et al (2002), Yang and Tarng (1998), and Davim and Figueira (2006). For example, higher speed accelerated tool wear and increased the cutting temperature of the ceramic tool when machining the hardened AISI M2 steel (Jang and Hsiao, 2000).…”
Section: Analysis Of Control Factorsupporting
confidence: 93%
See 2 more Smart Citations
“…It was concluded that the cutting speed was found to be the most important parameters on the tool life among control parameters. Similar results were obtained with previous works carried out by Lima et al (2005), Jang and Hsiao (2000), Sahin and Sur (2005), Sahin (2006), Benga and Abrao (2003), Chou et al (2002), Yang and Tarng (1998), and Davim and Figueira (2006). For example, higher speed accelerated tool wear and increased the cutting temperature of the ceramic tool when machining the hardened AISI M2 steel (Jang and Hsiao, 2000).…”
Section: Analysis Of Control Factorsupporting
confidence: 93%
“…Similar results were obtained with previous works carried out by Lima et al (2005), Jang and Hsiao (2000), Sahin and Sur (2005), Sahin (2006), Benga and Abrao (2003), Chou et al (2002), Yang and Tarng (1998), and Davim and Figueira (2006). For example, higher speed accelerated tool wear and increased the cutting temperature of the ceramic tool when machining the hardened AISI M2 steel (Jang and Hsiao, 2000). It was reported that the cutting speed was the most dominant factor affecting the tool life when turning of hardened 100Cr6 bearing steel (Benga and Abrao, 2003, Davim 2001, Davim and Figueira 2006.…”
Section: Analysis Of Control Factorsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous studies have been reported on the successful implementation of hard turning. Most of these studies involve work materials with hardness values in the range of 52-62 HRC and also they involve the use of ceramic, CBN and PCBN cutting tools [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, three v c values and two values of f were adopted. Based on the results of dynamic stability tests performed by Jang & Hsiao [25] under similar conditions to those used in this work and, in order to avoid the influence of vibrations during the experiments, ap = 0.3 mm was adopted.…”
Section: Methodsmentioning
confidence: 99%